Initial Market Assessment : Country Scoping Note--Bangladesh - World Bank (Washington, DC, 2015)
Bangladesh has a comprehensive Disaster Management plan, but details on the implementation and sufficiency of funding should be clarified. Strengthening financial disclosure could encourage greater engagement from key local and international stakeholders. The country also offers great opportunities to increase the outreach of insurance to larger sections of the population, especially to those most vulnerable to the substantial exposure to natural hazards and especially flood. The micro-finance market is well developed and provides opportunities to expand the still very limited availability of micro-insurance propositions to the rural population. Index-based insurance programs supported by mobile payment systems have already been piloted and there is considerable scope for this to be expanded, especially when appropriately subsidized to address affordability issues. However, this will require further strengthening of the insurance market, in respect of the implementation of the Insurance Act 2010 and of consumer representation, which is underdeveloped but may contribute strongly to improve the public’s confidence and help the industry to develop successful propositions also for emerging customers.